Conduct Disorder In Middle School Students (Build And Apply) - Jalil Abbas, Haidar; Halal Ali, Ali (Opción, 2019)
The current research aims to identify the disorder of the course at the request of the intermediate stage, as the research consisted of (1000) students and stu- dents of the intermediate stage. The researcher built the measure of distur- bance course based on the fifth American diagnostic guide for mental and mental disorders (2015: DSM _5) The researcher used the statistical methods: T-test for one sample (T _test), T-test for two independent samples, Pearson correlation coefficient, and the results of the current research N request the intermediate stage have the course of disorder, and there are statistically sig- nificant differences in the level of behavior disorder, and in the light of the findings of the researcher presented a number of recommendations and sug- gestions.